Geomorfologi Daerah Botubarani dan sekitarnya, Kabupaten Bone Bolango - Monawati Hasan; Yayu Arifin; Siti Marina (-, 2026)
This research was conducted to identify geomorphological units and analyze the characteristics of land form in the Botubarani region and its surroundings, Bone Bolango Regency, as the basis for understanding the development of natural landscapes and spatial planning in coastal areas. This analysis is carried out through the interpretation of topographic maps, DEM data and field observations to explain the relationship between lithology, geological structures and geomorphic processes that form the landscape. The research results show that Botubarani and its surroundings are composed of four main landforms, namely, intrusion hills, volcanic hills, denudational hills and aluvial plains. Variations in altitude, slope slope and river flow patterns illustrate the influence of longitudinal topography, resistant rocks and active exogenous processes. This finding shows that the geomorphological diversity of Botubarani is the result of the interaction between past tectonic activity, lithological character, and continuous surface processes. This research provides a more detailed and relevant geomorphological mapping to support the study of environmental vulnerability, hazard mitigation, and coastal area utilization planning.